Optimizing coral reef monitoring: species traits and habitat factors predict visual census performance - Iris M. George; Alexandra C. D. Davis; John L. Akins; Allison C. Candelmo; Stephanie J. Green (Coral Reefs, 2026)

Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Aylin Ulman; Fadilah Z. Ali; Holden E. Harris; Mohammad Adel; Sara A. A. Al Mabruk; Michel Bariche; Allison C. Candelmo; Jennifer K. Chapman; Burak Ali Çiçek; Kaylin R. Clements; Alexander Q. Fogg; Stacy Frank; et al. (Frontiers in Marine Science, 2022)
Major invasions of Indo-Pacific lionfish ( Pterois volitans and P. miles ) are underway in the Western Atlantic Ocean and the Mediterranean Sea. While the establishment of lionfish in the Western Atlantic is perhaps the most well-studied marine fish invasion to date, the rapidly expanding invasion in the Mediterranean is more recent and has received less attention. Here we review and synthesize successes and failures from two decades of lionfish management in the Western Atlantic to give policy recommendations for their management in the Mediterranean. Two failed approaches that were attempted multiple times in the Western Atlantic and that we advise against are (1) feeding lionfish to native fish to promote predation and (2) implementing bounty programs to incentivize lionfish harvest. Broadly, the most important management lessons that we recommend include (1) conducting routine removals by spearfishing with scuba, which can effectively suppress local abundances of lionfish; (2) encouraging the development of recreational and commercial lionfish fisheries, which can promote long-term, sustainable lionfish population control; and, (3) engaging local communities and resource users (e.g., with lionfish removal tournaments), which can concurrently achieve multiple objectives of promoting lionfish removals, market-development, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba was otherwise prohibited for conservation purposes. The risk of abusing these policies was mitigated through the use of gear restrictions, diver trainings, and through participatory approaches that integrated scuba divers and stakeholder organizations in lionfish research and management. Our review of policies and practices in the Mediterranean Sea found that many of our recommended lionfish management approaches are not being done and indicate potential opportunities to implement these. We expect and fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control will require rapid and strategic management approaches with broad cooperation among and between governments and stakeholders.

Ocean and Coastal Acidification off New England and Nova Scotia - Dwight Gledhill; Meredith White; Joe Salisbury; Helmuth Thomas; Ivy Misna; Matthew Liebman; Bill Mook; Jason Grear; Allison Candelmo; R. Christopher Chambers; Christopher Gobler; Christopher Hunt; et al. (Oceanography, 2015)

A National Assessment of Stressors to Estuarine Fish Habitats in the Contiguous USA - Correigh M. Greene; Kristan Blackhart; Joe Nohner; Allison Candelmo; David Moe Nelson (Estuaries and Coasts, 2015)

The Effect of Contaminated Prey on Feeding, Activity, and Growth of Young-of-the-Year Bluefish, Pomatomus saltatrix, in the Laboratory - Allison C. Candelmo; Ashok Deshpande; Bruce Dockum; Peddrick Weis; Judith S. Weis (Estuaries and Coasts, 2010)